Life is viewed as better for minorities in places with more variable habitats - Evert Van de Vliert; Mohsen Joshanloo; Lucian G. Conway III; Esther S. Kluwer; Paul A. M. Van Lange (PLoS ONE, 2025)
Places differ in how livable they are perceived to be for minority groups. But why? We pursue an explanation through the lens of natural habitat variability (varying day length, temperature, and daily precipitation over the course of the year). Uncertainty reduction theory, flexible systems theory, and climato-economic theory offer different explanations for how habitat variability influences mindsets about racial and ethnic minorities, gays and lesbians, foreign immigrants, and people with intellectual disabilities. To test our hypotheses, we analyzed the perceived livability of the place of residence for these minority groups by 1,332,558 native inhabitants from 163 countries. Our results support the theoretical notion that variable habitats foster flexible psychosocial systems. Minorities are viewed to have better livability in places with more variable habitats. Economic affluence reinforces this trend, and the interaction effect is mediated by the quality of governance. These country-level findings (R2 ≈ 0.52) demonstrate construct, concurrent, convergent, divergent, substantive, and forecast validity. They significantly overshadow effects of individual-level characteristics and mindsets (R2 ≈ 0.03). Habitat equations predicting perceived local livability for minorities during one period (2010–2015) forecast up to 75 percent of the extent to which minorities in each of the four hemispheres of the Earth are perceived to be living in a good place at a subsequent period (2016–2020).